Optimizing the Performance of the Kudus Police Satreskrim in Handling Online Fraud to Increase Crime Clearance - Aji, Gagas Dewanta (Advances in Police Science Research Journal, 2024)
Along with the rapid development of technology, online fraud is rampant in Kudus Regency. It takes handling carried out by Satreskrim Polres Kudus to achieve ideal conditions and the expected goal, namely increasing the settlement of cases handling online fraud crimes. This research aims to describe the performance of investigations by Satreskrim Polres Kudus in handling online fraud crimes and explain the factors that influence the performance of investigations by Satreskrim Polres Kudus in handling online fraud crimes. This research was conducted using a qualitative approach to data collection techniques of interviews, observation, and documentation studies. The results of the study found that the settlement of online fraud cases at the Kudus Police was still nil. The performance of investigations by Satreskrim Polres Kudus has not been able to reveal the criminal act of online fraud due to the lack of ability of personnel who are experts in the field of ITE and ITE special tools needed. Besides being limited by regulations, the main obstacle faced is that investigators have difficulty profiling and tracking the whereabouts of the perpetrators. Based on the results of the research, the handling of online fraud crimes by the Kudus Police Satreskrim to increase case completion has not been optimal. It is necessary to propose members of the Satreskrim Polres Kudus carry out cybercrime specialization development education, procure special ITE tools, and form MoUs with related parties so that the hope of increasing the settlement of online fraud cases is achieved.